Penggunaan Pemodelan Paru-Paru sebagai Upaya Meningkatkan Pemahaman Peserta Didik tentang Mekanisme Pernapasan di Kelas VIII.8 MTsN 2 Kota Bima - Salmi Salmi (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2022)
Process of learning science, teaching is not just explaining explanations and demonstrations, it will not produce lasting learning outcomes. Only active learning activities can produce lasting learning outcomes. Therefore the teacher must have a strategy so that students can learn effectively and efficiently, hit the expected goals. By realizing this fact, a classroom action research was conducted to increase students' understanding of the mechanism of breathing using the lung model in Class VIII.8 MTsN 2 Kota Bima. The point of concern of this research is to improve the quality of learning science, in particular to improve the learning process and the results of understanding the mechanism of breathing using the lung model for students. From the results of this study it can be concluded that the use of the lung model can improve the ability to understand the mechanism of breathing for students in class VIII.8 MTsN 2 Kota Bima, as evidenced by the increase in the achievement of individual scores for each student.